2,4-Dihydroxy-5-Bromovalerophenone Oximes as a Gravimetric Reagent for Ni(II) and Cu(II) and Spectrophotometric Study of Complexes - Patel, N.B.; Desai, K.K. (Asian Journal of Chemistry, 2012)
2,4-Dihydroxy-5-bromovalerophenone oxime (DHBVO) was developed as a new analytical reagent for the gravimetric estimation of divalent nickel and copper ions. In pH range of 3.0 to 6.0, this reagent gives a buff colored precipitate with Cu2+. Job’s method and mole ratio method revealed that the stoichiometry of the complex is 1 : 2, the beer’s law is obeyed up to 38.12 ppm of Cu2+. The molar absorptivity at 420 n was found to be 5.31 × 102 L mol-1 cm-1. The stability constant of the complex is found to be 1.885 × 109. Ni2+ gives light green colored precipitate in pH range 7.0 to 9.0. Using both the above-mentioned methods, it was found that stoichiometry was 1 : 2. The molar absorptivity at 440 nm was found to be 1.79 × 102 L mole-1 cm-1. The stability constant of the complex found to be 1.24 × 109. Beer’s law is obeyed upto 35.22 ppm of Ni2+. The reagent can be used for the analysis of German silver alloy.